Potential of Using High Rate Algal Pond for Algal Biofuel Production and Wastewater Treatment - Doma, Hala S.; El-Liethy, M. Azab; Abdo, Sayeda M.; Ali, Gamila H. (Asian Journal of Chemistry, 2015)
The aim of this study is to investigate the application of high rate algal pond for municipal wastewater treatment and the production of microalgae biomass for biofuel production. Primary facultative pond one cubic meter (1 m3) followed by high rate algal pond (1.5 m3) were installed in wastewater treatment plant and fed with municipal wastewater. High rate algal pond enhance the removal of nutrients, organic contaminants, coliforms and E. coli. The performance data of the treatment system showed that the removal efficiency of COD, BOD, total suspended solids and ammonia were 31, 33, 22 and 56 %, respectively. The removal of total coliforms reached up to 3 logs. Furthermore, fecal coliforms and E. coli removal reached 3 and 5 logs, respectively. The community structure of the high rate algal pond revealed that the most dominant algal species were Scenedesmes obliquus and Micracitinium pusillum. The total lipid percentage was an average of 5 % in the high rate algal pond. The gas chromatographic analysis of the fatty acid methyl ester revealed that stearic acid (C18:0) concentration reached up to 18.8 %, the oleic acid and linolenic acid were detected with an average percentage of 10.3 % and 13.8 %, respectively. It can be concluded that, the high rate algal pond considered as an efficient and cost-effective pond system for municipal wastewater treatment. Also, it able to produced oil used as biodiesel source from the biomass of the harvested microalgae.